Optimal cash holding model based on minimization of ruin probability - Zhengyan Wang; Yan Zhang; Peibiao Zhao (Miskolc Mathematical Notes)
The management of optimal cash holding is particularly important for the sustainability of enterprises’ survival and business decision-making. It is not good for enterprises to have more or less cash holding. In the meantime, the probability of enterprise bankruptcy is also one of the most important research topics in the field of economic finance and management science, such as the early warning of investment risk and financial decision support. In this paper, an optimal cash holding model is established. It is assumed that the objective of optimal cash holding is to minimize the probability of bankruptcy and the security area of cash holding is the constraint condition. By using the dynamic stochastic programming method, the optimal conversion strategy and the analytic expressions of the value function are obtained, and the relevant economic explanations and numerical examples are given. The effects of capital market parameters and consumption function parameters on the optimal conversion strategy and optimal cash holding are discussed.